Two Polo-like kinase 4 binding domains in Asterless perform distinct roles in regulating kinase stability. - Klebba, J.E.; Galletta, B.J.; Nye, J.; Plevock, K.M.; Buster, D.W.; Hollingsworth, N.A.; Slep, K.C.; Rusan, N.M.; Rogers, G.C. (Journal of Cell Biology, 2015)
Plk4 (Polo-like kinase 4) and its binding partner Asterless (Asl) are essential, conserved centriole assembly factors that induce centriole amplification when overexpressed. Previous studies found that Asl acts as a scaffolding protein; its N terminus binds Plk4's tandem Polo box cassette (PB1-PB2) and targets Plk4 to centrioles to initiate centriole duplication. However, how Asl overexpression drives centriole amplification is unknown. In this paper, we investigated the Asl-Plk4 interaction in Drosophila melanogaster cells. Surprisingly, the N-terminal region of Asl is not required for centriole duplication, but a previously unidentified Plk4-binding domain in the C terminus is required. Mechanistic analyses of the different Asl regions revealed that they act uniquely during the cell cycle: the Asl N terminus promotes Plk4 homodimerization and autophosphorylation during interphase, whereas the Asl C terminus stabilizes Plk4 during mitosis. Therefore, Asl affects Plk4 in multiple ways to regulate centriole duplication. Asl not only targets Plk4 to centrioles but also modulates Plk4 stability and activity, explaining the ability of overexpressed Asl to drive centriole amplification.